Persepsi Dan Kemampuan Perawat Menggunakan Buku Saku Perawat Pada Penatalaksanaan Penyakit Paru Dan Gangguan Sistem Pernafasan Di Puskesmas Rawat Jalan - Meta Margaretna; Mustiah Yulistiani (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To identify the characteristich of respondents, nurses’ perception and ability in using nurses’ pocketbooks on the management of pulmonary disease and respiratory system disorder.Method: This research uses analytic descriptive method. The sample consist of 30 respondents taken through total sampling. The research instrument are questionnaires and observation sheets.Results: Most of the respondents are female (70%). The respondents' age is mostly the early adulthood and late adulthood (30%). The respondents' education level is associate (80%), having long work years of service (36.7).Moreover, it is also obtained that the respondents have an excellent perception (60%) and good ability (100%).Conclusion: In carrying out documentation using nurses' pocketbooks on the management of pulmonary disease and respiratory system disorder, this research indicates that the nurses' perception is excellent and their ability is good in using the pocketbook. This is supported by the nurses' education level, in which most of them are associate, and by their long years of service, more than 5 years.